Models and Methods of Continuing Education for Christian Ministry in the Religiously Plural Context - Mosher, Lucinda (Teaching theology and religion, 2006)
This paper asserts that Continuing Education aimed at equipping Christian leaders (lay and ordained) to carry out their ministries in the midst of America's increasing religious diversity in a way that views this diversity positively must be two-pronged: (1) it must provide accurate information about the beliefs and practices of the neighbors, and (2) it must provide theological resources rooted in Christian scripture and tradition. As this paper explores a variety of models, it reflects on the difficulty of holding these two goals together and the problems inherent in attempting to measure what such Continuing Education programs and events accomplish. In considering ways forward, it offers a Christian theology of religious difference informed by notions of neighbor-love.